Difficulties in the identification of corpses and skeletal remains by Forensic Odontology in Costa Rica: Analysis of 165 autopsies - Fernández Chaves, José Manuel (2022)
Introduction: In Costa Rica the elaboration of dental records or clinical files is not performed routinely in all patients as it is required by law in many countries. The completion of the dental record is only regulated by the Code of Ethics of the Colegio de Cirujanos Dentistas de Costa Rica (Board of Dental Surgeons of Costa Rica), which means that failure to do so is considered an ethical-disciplinary offense with few consequences for the professional; however, it has serious consequences in the efforts to identify a person. This study aims to describe the impact of the absence or poor quality of antemortem data in identification cases performed by the Forensic Odontology Unit of the Department of Legal Medicine over a period of almost eight years (2015-2022). Materials and Methods: A detailed review was performed in the database of the Forensic Medicine System (SIMEL) of the Legal Medicine Department of the Judicial Investigation Organism of the totality of interconsultation requests of the Forensic Pathology Section from January 2015 to August 2022. The information collected was tabulated in Excel and included both the results of the expert analysis and the characteristics of the available antemortem information. Results: The analysis of the data made it possible to determine that in a period of almost 8 years 165 assessments were carried out for identification purposes, of which 51 individuals were identified, 9 cases presented insufficient information and 105 had no dental files. Conclusions: A complete dental record is indispensable for a positive identification; an incomplete or non-existent record nullifies the possibility of identifying a human being.